Acute kidney injury among paediatric emergency room admissions in a tertiary hospital in South West Nigeria: a cohort study (2019)
Background. Epidemiological data on paediatric acute kidney injury (AKI) in sub-Saharan Africa are limited and largely retrospective. We performed a prospective study of AKI among patients admitted through the emergency room. Methods. Children admitted to the post-neonatal emergency room of the University College Hospital, Ibadan, Nigeria between February 2016 and January 2017 were studied. AKI was defined by Kidney Disease: Improving Global Outcomes serum creatinine criteria. AKI ascertainment relied on serum creatinine measurements carried out in routine care by post admission Day 1. We compared in-hospital mortality by post-admission Day 7 for patients with and without AKI (no-AKI). Results. Of the 1344 children admitted to the emergency room, 331 were included in the study. AKI occurred in 112 patients (33.8%) with a median age of 3.1 years [interquartile range (IQR) 0.9–9.4] and was Stage 3 in 50.5% of the cases. The no-AKI group had a median age of 1.8 (IQR 0.7–5.8) years. The underlying diagnoses in patients with AKI were sepsis (33.0%), malaria (12.5%) and primary renal disorders (13.4%). Twenty-four of the patients with AKI underwent dialysis: haemodialysis in 20 and peritoneal dialysis in 4. By Day 7 of admission, 7 of 98 (7.1%) patients in the AKI group had died compared with 5 of 175 (2.9%) patients in the no-AKI group [odds ratio 2.6 (95% confidence interval 0.8–8.5)]. Outcome data were not available for 58 (17.5%) patients. Conclusions. AKI is common among paediatric emergency room admissions in a tertiary care hospital in sub-Saharan Africa. It is associated with high mortality risk that may be worse in settings without dialysis.